2009
DOI: 10.1146/annurev.ecolsys.110308.120209
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Placentas in the Fish Family Poeciliidae: An Empirical Study of Macroevolution

Abstract: The placenta is a complex organ that mediates all physiological and endocrine interactions between mother and developing embryos. Placentas have evolved throughout the animal kingdom, but little is known about how or why the placenta evolved. We review hypotheses about the evolution of placentation and examine empirical evidence in support for these hypotheses by drawing on insights from the fish family Poeciliidae. The placenta evolved multiple times within this family, and there is a remarkable diversity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
259
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(268 citation statements)
references
References 90 publications
(172 reference statements)
6
259
0
3
Order By: Relevance
“…Moreover, variation in adult brain mass and structure across species reflects species differences in both prenatal and postnatal growth (Leigh 2004). The placenta is believed to be a major site for the evolutionary arms race between maternal and paternal genes over maternal allocation of resources to the developing offspring (Haig 1993;Crespi and Semeniuk 2004;Pollux et al 2009). Several studies have shown that imprinted genes are particularly important in this context, with expressed genes of paternal origin promoting placental and fetal growth beyond the optimum for maternal interests, and expressed genes of maternal origin acting antagonistically to paternally expressed genes and generally restricting placental and fetal growth (see reviews in Riek et al 2003;Crespi and Semeniuk 2004;Angiolini et al 2006;Petry et al 2007;Vrana 2007;Bressan et al 2009;Ng et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, variation in adult brain mass and structure across species reflects species differences in both prenatal and postnatal growth (Leigh 2004). The placenta is believed to be a major site for the evolutionary arms race between maternal and paternal genes over maternal allocation of resources to the developing offspring (Haig 1993;Crespi and Semeniuk 2004;Pollux et al 2009). Several studies have shown that imprinted genes are particularly important in this context, with expressed genes of paternal origin promoting placental and fetal growth beyond the optimum for maternal interests, and expressed genes of maternal origin acting antagonistically to paternally expressed genes and generally restricting placental and fetal growth (see reviews in Riek et al 2003;Crespi and Semeniuk 2004;Angiolini et al 2006;Petry et al 2007;Vrana 2007;Bressan et al 2009;Ng et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, gestation length is reduced where sibling competition, which exacerbates maternal-offspring conflict, is more intense (Stockley and Parker 2002). Maternal-offspring conflict theory predicts that larger litters and greater levels of female promiscuity, which increase sibling competition due to the lower relatedness among littermates and so selection on paternally expressed genes, should lead to greater maternal-offspring conflict and be associated with the evolution of placental morphologies promoting nutrient transfer (Trivers 1974;Haig 1993;Vrana 2007;Pollux et al 2009;Zeh and Zeh 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not apply to the independent evolution of viviparity in freshwater fishes (Pollux et al 2009) and amphibians (Vitt and Caldwell 2013). In viviparous lizards and snakes, gravid females actively thermoregulate and provide embryos of higher temperatures for development, a behaviour that reduces juvenile mortality as compared to conditions in nest regimes (Braña et al 1991).…”
Section: Reptilesmentioning
confidence: 99%
“…Poeciliine species bear their young as free-swimming juveniles (without a yolk sac), and exhibit either ovoviviparity (eggs hatch within the uterine cavity), or viviparity (maternal provisioning to the developing larvae while in the uterine cavity). The ovoviviparity condition is thought to be derived within the subfamily (Pollux et al, 2009). One poeciliine species, Tomeurus gracilis from northeastern South America, is facultatively ovoviviparous, releasing eggs or live young depending on environmental conditions (Breder & Rosen, 1966;Wourms, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Poeciliids are characterized by a suite of derived characters including the position of the pectoral fins high on side of the body, an anterior placement of the pelvic fins ventral to the pectoral fins, the presence of pleural ribs on the first several haemal arches, a bony cap on the ventral hypohyal lying over the anterior facet of the anterior ceratohyal, and supraorbital laterosensory pores with neuromasts embedded in fleshy grooves (Ghedotti, 2000). Despite the widespread use of poeciliid fishes in ecological and evolutionary studies (e.g., Rauchenberger, 1990;Meyer et al, 1994;Borrowsky et al, 1995;Marcus & McCune, 1999;Spencer et al, 1999;Spencer et al, 2000;Morris et al, 2001;Kallman et al, 2004;Gutierrez-Rodriguez et al, 2007a, 2007bReznick et al, 2007;Leberg & Firmin, 2008;Purcell et al, 2008;Martin et al, 2009;Pollux et al, 2009;Meredith et al, 2010;Pires et al, 2010;Albert & Johnson, 2011), the phylogenetic interrelationships among poeciliid species remain incompletely resolved.The family Poeciliidae comprises three subfamilies that are restricted to fresh and brackish continental waters: Poeciliinae, Procatopodinae, and Aplocheilichthyinae (Ghedotti, 2000;Lucinda, 2003;Hrbek et al, 2007). The Poeciliinae includes at least 228 species distributed across much of the tropical and subtropical portions of the Americas, from the La Plata estuary of northern Argentina to southeastern United States, with species richness reaching a zenith in Middle America and the West Indies (Rosen & Bailey, 1963;Lucinda, 2003;Hrbek et al, 2007;.…”
mentioning
confidence: 99%